Antiatherosclerotic and Cardioprotective Potential of Acacia senegal Seeds in Diet-Induced Atherosclerosis in Rabbits - Heera Ram; Rameshwar Jatwa; Ashok Purohit (Biochemistry Research International)
Acacia senegal L. (Fabaceae) seeds are essential ingredient of “Pachkutta,” a specific Rajasthani traditional food. The present study explored antiatherosclerotic and cardioprotective potential of Acacia senegal seed extract, if any, in hypercholesterolemic diet-induced atherosclerosis in rabbits. Atherosclerosis in rabbits was induced by feeding normal diet supplemented with oral administration of cholesterol (500 mg/kg body weight/day mixed with coconut oil) for 15 days. Circulating total cholesterol (TC), HDL-cholesterol (HDL-C), LDL-cholesterol (LDL-C), triglycerides, and VLDL-cholesterol (VLDL-C) levels; atherogenic index (AI); cardiac lipid peroxidation (LPO); planimetric studies of aortal wall; and histopathological studies of heart, aorta, kidney, and liver were performed. Apart from reduced atherosclerotic plaques in aorta (6.34±0.72) and increased lumen volume (51.65±3.66), administration with ethanolic extract of Acacia senegal seeds (500 mg/kg/day, p.o.) for 45 days to atherosclerotic rabbits significantly lowered serum TC, LDL-C, triglyceride, and VLDL-C levels and atherogenic index as compared to control. Atherogenic diet-induced cardiac LPO and histopathological abnormalities in aorta wall, heart, kidney, and liver were reverted to normalcy by Acacia senegal seed extract administration. The findings of the present study reveal that Acacia senegal seed extract ameliorated diet-induced atherosclerosis and could be considered as lead in the development of novel therapeutics.